Quarter-Symmetric Nonmetric Connection on P-Sasakian Manifolds. (3rd December 2012) - Mondal, Abul Kalam; De, U. C.
Abstract : The object of the present paper is to study a quarter-symmetric nonmetric connection on a P -Sasakian manifold. In this paper we consider the concircular curvature tensor and conformal curvature tensor on a P -Sasakian manifold with respect to the quarter-symmetric nonmetric connection. Next we consider second-order parallel tensor with respect to the quarter-symmetric non-metric connection. Finally we consider submanifolds of an almost paracontact manifold with respect to a quarter-symmetric non-metric connection.